2009
DOI: 10.1111/j.1365-2834.2009.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

What health care managers do: applying Mintzberg’s structured observation method

Abstract: Aim The aim of the present study was to explore and describe what characterizes first- and second-line health care managers' use of time. Background Many Swedish health care managers experience difficulties managing their time. Methods Structured and unstructured observations were used. Ten first- and second-line managers in different health care settings were studied in detail from 3.5 and 4 days each. Duration and frequency of different types of work activities were analysed. Results The individual variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 20 publications
1
90
0
3
Order By: Relevance
“…A similar trend has been spotted in several public sector domains in Sweden, as well as in other countries (e.g., Hagerman, 2014;Levin & Fullan, 2008;Rapp, 2010;Wolmesjö, 2008). New public management (NPM) ideals may be one reason for the increase of administrative tasks linked to accountability and the continuously scrutinizing of processes, improvements, performance, results, costs, and customer satisfaction (Abma & Noordegraaf, 2003;Pollitt & Bouckaert, 2000) at the same time as the direct administrative support often has decreased (Arman et al, 2009;Höckertin, 2007). Although a high workload can constitute a positive challenge in a job (Crawford et al, 2010), work overload has been associated with ill-health (e.g., Schaufeli & Bakker, 2004).…”
Section: Workload Became Work Overloadmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend has been spotted in several public sector domains in Sweden, as well as in other countries (e.g., Hagerman, 2014;Levin & Fullan, 2008;Rapp, 2010;Wolmesjö, 2008). New public management (NPM) ideals may be one reason for the increase of administrative tasks linked to accountability and the continuously scrutinizing of processes, improvements, performance, results, costs, and customer satisfaction (Abma & Noordegraaf, 2003;Pollitt & Bouckaert, 2000) at the same time as the direct administrative support often has decreased (Arman et al, 2009;Höckertin, 2007). Although a high workload can constitute a positive challenge in a job (Crawford et al, 2010), work overload has been associated with ill-health (e.g., Schaufeli & Bakker, 2004).…”
Section: Workload Became Work Overloadmentioning
confidence: 99%
“…Recent evidence from the human service sector points to a troublesome work situation, and to the problems of attracting and retaining skilled managers (Arman et al, 2009;Corin et al, 2016;Danielson et al, 2012;Höckertin, 2007;Skagert et al, 2012). First-line managers of human service organizations are particularly exposed and in disadvantageous work situations (e.g., Berntson et al, 2012;Björk, 2013).…”
mentioning
confidence: 99%
“…Choi, Sung & Kim (2010) and Kobasa & Puccetti (1983) found that support from higher-level managers played a key role in overcoming major challenges. However, Arman, Wikström & Dellve (2009) pointed out that Healthcare managers spend a relatively small amount of time with their own senior managers. Several studies also show that Healthcare managers often refrain from seeking assistance and support because of a fear that this may have a negative impact on their career development (Tengelin, Kihlman, Eklöf & Dellve, 2011).…”
Section: Social Supportmentioning
confidence: 99%
“…Choi et al (2010) concluded in an empirical study on how groups reacted to unexpected threats that support from the superior manager played a key role in the organizations' ability to overcome crises. However, according to Dellve et al (2013) and Arman et al (2009) support from superior managers is often lacking managers. In the present study, superior managers were identified as a potential source of support, but they seldom fulfilled that function for the managers interviewed.…”
Section: Managers' Strategies For Self Protectionmentioning
confidence: 99%
“…Eles abordaram uma grande variedade de temas como: o que fazem os administradores de sucesso (contatos externos e socialização, gestão de conflitos, tomada de decisão e planejamento); metodologias empregadas (observação estruturada, diários e auto-observação); as características distintivas das tarefas do administrador (interdependência, ausência de padrão, inovação e resultados indiretos); relações com a estrutura organizacional (grau de centralização e descentralização, divisão de trabalho e autonomia); os efeitos das mudanças nas estruturas organizacionais sobre o trabalho do administrador (estruturas burocráticas e em rede); o trabalho do administrador nos serviços de atenção à saúde (médicos e enfermeiras); replicação dos estudos clássicos (Mintzberg, 1973e Carlson, 1951; preferências dos administradores (liderar empregados, relacionamento e inovação); revisão teórica de abordagens (Fayol e Mintzberg); o trabalho do administrador na área de educação (faculdades, universidades, públicas e privadas); os papéis administrativos dos profissionais de tecnologia da informação (diretores executivos em empresas norueguesas); e o desempenho da informação no trabalho do administrador (relação entre contexto, trabalho do administrador e importância da informação) (LUTHANS; ROSENKRANTZ;HENNESSEY, 1985;MARTINKO;GARDNER, 1985;WHITLEY, 1989;HALES;TAMANGANI, 1996;HALES, 2002;ARMAN et al, 2009;TENGBLAD, 2002TENGBLAD, , 2006KONRAD et al, 2001;LAMOND, 2003;MECH, 1997;LAITINEN, 2009). 2.2 Características e a Natureza do Trabalho do Administrador Segundo Mintzberg (1986, a escola clássica da administração, representada por Fayol e seus seguidores, caracteriza o administrador como um planejador reflexivo e sistemático; dependente de informações agregadas, cuja melhor fonte é um sistema formal; gestor de relações hierárquicas entre um "superior" e seus "subordinados"; e um controlador rígido de seu tempo, de suas atividades, de suas unidades.…”
Section: O Trabalho Do Administradorunclassified